Robert Ludlum's The Treadstone rendition - Hood, Joshua (New York : G.P. Putnam's Sons, 2024)
Adam Hayes has stepped away from the field for the last time. He's promised his wife that he won't put his life on the line any more, and there's nothing that will make him break a promise to his wife. Well...almost nothing. With America withdrawing from Afghanistan and the Taliban closing in, Abdul Nassir reached out to his old friend. Ten years ago, he saved the American's life, and the time has come for repayment. The Afghan is desperate to flee his homeland. Like most of his countrymen, he is petrified by the Taliban takeover, but he also can't trust the Americans. He's the only eyewitness to a massacre committed by a rogue team of CIA contractors. Not only can he identify the butcher who directed the bloodbath, he also has photographic proof. He'll only be safe when those pictures are made public. Now, there's just one man he can trust to get him to safety.
Includes an excerpt from The Bourne evolution.
Keywords: Contractors -- Fiction; Afghanistan -- Fiction; Action and adventure fiction; Thrillers (Fiction)